OBSERVING IDEOLOGY IN CRITICAL DISCOURSE ANALYSIS THROUGH CRITICAL LITERACY PRACTICE - Ainun Nisa Luthfi Salsabila; Indah Arvianti; Didit Kurniadi (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
By revealing speakers’ meanings through ideology, this project aims to provide the gaps in critical discourse analysis abilities through critical literacy practice. Because of the power of legislators, political figures, and other text creators, language preferences can be used to oppress the broader population. Readers should be open to critically evaluating all texts to prevent the media from controlling what they read. The community may experience social chaos as a result of students’ inability to comprehend and analyse news and mass media. The ruling party’s ideology, which seeks to uphold and defend its dominance, can be examined using critical discourse analysis to identify the power of language. The research uses a case study method that gathers data through artefacts and observation. Getting an explanation of students’ responses to questions, and the artefacts they have produced that show their engagement with critical literacy as Freire’s concept are all part of the data analysis process. The conceptual framework for teaching ideology fulfils the absence of emphasising critical literacy pedagogy, such as familiarising teaching methods, picking authentic materials, observing critical discourse analysis, applying multimodality, and asking critical questions. These conceptual frameworks can be used to teach students how to read and evaluate texts so they can learn about identity, diversity, and power. Students seem to benefit from critical literacy practice as a tool for developing critical language awareness, so they are not easily provoked by the text and obverse deeper the words they read before taking action that provides possibilities for social conflict. Therefore, the objective of this research is to develop language learning tools based on critical discourse analysis, with ideology as the core of revealing the meaning of speakers that provide critical literacy awareness. Keywords: critical discourse analysis, critical literacy, ideology